Skrining Gizi Balita dan Peningkatan Pengetahuan Ibu tentang MP-ASI di Posyandu Cempaka Kelurahan Pojok Kota Kediri - Halimatus Saidah; Fensentia Bai; Lidia Marsiani Moa; Resica Nur Hidayah; Amelia Nuril Madina; Galuh Pradian Yanuaringsih; Putri Wahyu Wigati; Sutrisni; Dhita Kris Prasetyanti; Maria Fatima Manang (UNIVERSITAS KADIRI, 2025)
Toddlers are a vulnerable age group for nutritional problems due to their rapid growth and the need for appropriate dietary support. Limited maternal understanding of food selection and feeding practices often contributes to the occurrence of undernutrition. This community service activity aimed to conduct nutritional screening for toddlers and improve mothers’ knowledge regarding healthy feeding practices in Pojok Village, Kediri City. The methods consisted of preparation, nutritional screening through anthropometric measurements, practical-based nutrition education, and evaluation of maternal knowledge through pre- and post-education assessments. The screening results showed that 80 percent of toddlers were in the good nutritional category, while 20 percent were classified as undernourished. Knowledge evaluation demonstrated an increase in maternal understanding, indicated by the rise in the proportion of mothers with good knowledge from 20 percent before the education session to 75 percent afterward. These findings indicate that the implemented education successfully helped mothers understand healthy feeding practices at home and strengthened their ability to support adequate nutritional intake for their children. In conclusion, the integration of nutritional screening and education proved effective in enhancing family awareness and understanding of toddler nutrition. These results highlight the importance of strengthening promotive and preventive efforts within community health services.